Synthesis and structure of novel potentially bioactive amphiphilic -O-(N)-glycosides - Bejarano Rengel, Natividad Jhosselin (2020)
Herein we present the synthesis and structural analysis of novel -O-(N)-glycosides. The biphasic reaction of NHS and acetobromo-α-d-glucose or d-galactose gives the β anomer glycoside in a straightforward manner. Further hydrazinolysis and condensation with decanal afforded the desired products. Their complete structures, including the anomeric and E/Z double bond configurations, were determined by spectroscopic analysis.